The conflict of laws - Briggs, Adrian (Oxford : Oxford University Press, 2019)
This introduction to the study of the conflict of laws provides a survey and analysis of the rules of private international law as they apply in England. Written to take account of the various possible outcomes of the Brexit process, it goes as far as is possible to make sense of the effect it will have on English private international law. The volume covers general principles, jurisdiction, and the effect of foreign judgments; the law applicable to contractual and non-contractual obligations, the private international law of property, of adults (the increasingly complex law of children is described in bare outline), and of corporations. It does so in a manner which explains and illuminates the principles which underpin the subject in a clear and coherent fashion, as the wealth of literature, case law, and legislation can often obscure the architecture of the subject and unnecessarily complicate its study.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 15, 2019).
Keywords: Conflict of laws -- England; Conflict of laws -- Wales